Rozwiązane

(7^6*7^4)3/(7^12:7^8)^7=
(2^3*2^2)^3:2^12=
1000^7:125^7/64^3=
3^10:3^2/81=
Potrzebuje na teraz



Odpowiedź :

Korlek

Odpowiedź:

(7^6*7^4)3/(7^12:7^8)^7= [tex]\frac{3}{7^{18} }[/tex]

(2^3*2^2)^3:2^12= 8

1000^7:125^7/64^3= [tex]2^{39}[/tex]

3^10:3^2/81= [tex]3^{12}[/tex]

nie jestem pewna ostatniego....

Szczegółowe wyjaśnienie:

Magda

Odpowiedź:

[tex]\dfrac{(7^6*7^4)^3}{(7^{12}:7^8)^7}=\dfrac{(7^1^0)^3}{(7^4)^7}=\dfrac{7^{30}}{7^{28}}=7^{30-28}=7^2=49\\\\\\(2^3*2^2)^3:2^{12}=(2^5)^3:2^{12}=2^{15}:2^{12}=2^{15-12}=2^3=8\\\\\\\dfrac{1000^7:125^7}{64^3}=\dfrac{(1000:125)^7}{(8^2)^3}=\dfrac{8^7}{8^6}=8^{7-6}=8^1=8\\\\\\\dfrac{3^1^0:3^2}{81}=\dfrac{3^8}{3^4}=3^{8-4}=3^4=81[/tex]